1576. Risk of Clinical Tuberculosis (TB) Among Patients with Latent TB Infection (LTBI) Who Undergo Allogeneic Hematopoietic-Cell Transplantation (HCT). (26th November 2018) - Kusztos, Amanda E; Cheng, Matthew P; Bold, Tyler D; Ho, Vincent T; Glotzbecker, Brett E; Hsieh, Candace; Baker, Meghan A; Hammond, Sarah P; Baden, Lindsey R; Marty, Francisco M
Abstract: Background: Mycobacterium tuberculosis is a leading cause of morbidity and mortality worldwide. The risk of developing active TB in persons with hematological malignancies is higher than the general population. However, the magnitude and timing of this risk has not been determined in non-endemic settings after HCT. The purpose of this study was to evaluate treatment practices and active TB rates in a cohort of HCT recipients. Methods: A retrospective cohort study was performed of all adult patients who underwent HCT at Dana-Farber Cancer Institute between January 2010 and January 2015. Baseline characteristics and laboratory parameters were collected. LTBI diagnostic tests included purified protein derivative (PPD) and interferon-gamma release assays (IGRA). Baseline chest radiography, history of BCG vaccination, and previous LTBI therapy were documented. Institutional guidance recommends that LTBI treatment begins upon discharge or by Day +28 after HCT, whichever is first. Patients were followed until April 2018 for development of active TB. Results: In a cohort of 1, 288 HCT recipients, 44 (3.4%) had evidence of LTBI, with 43 positive PPD tests and one positive IGRA. Median age was 55 years (range 19–72); 24/44 (54.5%) were male and 28/44 (63.6%) were non-US-born. Nine (20%) patients were treated for LTBI before HCT. Of the remaining 35 patients, 11 (25%) were treated within 3 months of HCT, three (6.8%) initiated treatment later than 3 months post HCT, and 21 (47.7%) did not receive treatment for reasons including death ( n = 14, median survival 1.5 years from HCT) and treatment refusal ( n = 4). Three patients were lost to follow-up. Among patients who initiated treatment, isoniazid ( n = 10) and levofloxacin ( n = 4) were used for a median of 145 days (range 7–326). There were no cases of active TB in the whole HCT cohort during the study period, which included a combined 139 person-years of follow-up in 44 patients with LTBI, of which 68 person-years were contributed by untreated individuals. Conclusion: These data suggest that TB reactivation does not usually occur very early after HCT. LTBI therapy could be deferred in the immediate post-transplant setting and initiated once patients are clinically stable with a lower risk of synergistic hepatotoxicity. Disclosures: S. P. Hammond, Merck: Investigator, Research support